MOLECULAR PROPERTIES OF COPPER CLUSTERS (CIPEEX, 2025)
Copper has been widely used by humanity since ancient times, with historical records dating back to the Egyptians around 2600 BC, when it was applied in wound healing and water purification. Over centuries, copper has also been employed in medicine, biology, and engineering due to its antimicrobial activity and high thermal and electrical conductivity. In the modern era, where antimicrobial resistance poses a serious global health threat, copper nanoparticles and molecular clusters have attracted significant attention as potential alternatives to conventional antibiotics. In this study, we investigated the molecular and electronic properties of copper clusters Cu₇, Cu₈, and Cu₉ through computational simulations combining spectroscopic analysis with ab initio quantum mechanical methods. These approaches allowed us to evaluate the stability, coordination modes, and redox potential of the clusters, which are critical factors in their interaction with bacterial environments. The simulations revealed that Cu₇, Cu₈, and Cu₉ clusters exhibit strong electronic stability and the ability to undergo redox cycling between Cu(I) and Cu(II), enabling catalytic activity in Fenton-like reactions that generate reactive oxygen species (ROS). Such ROS, including hydroxyl radicals and superoxide anions, cause oxidative stress in bacterial cells, leading to lipid peroxidation, protein denaturation, and DNA fragmentation. This mechanism explains the Strong bactericidal effects observed in experimental studies of copper nanoparticles Against multidrug-resistant pathogens such as Staphylococcus aureus and Pseudomonas aeruginosa. Furthermore, the modeling results suggest that the size and atomic arrangement of the clusters directly influence their capacity to release copper ions and enhance ROS production. Taken together, these findings support the hypothesis that copper clusters can serve as highly effective antimicrobial agents, opening possibilities for their application in coatings for hospital environments, medical devices, and therapeutic formulations. The integration of computational spectroscopy with ab initio quantum mechanics proved to be a successful strategy to predict molecular behavior and validate experimental observations, reinforcing the importance of theoretical methods in the rational design of novel nanomaterials. Looking ahead, copper-based nanoparticles and clusters are expected to play an increasingly relevant role in the development of nextgeneration antimicrobial therapies capable of overcoming the growing challenge of antibiotic resistance.
Keywords: copper; nanoparticles; ROS; antimicrobal; quantum simulations